2020
DOI: 10.1111/jgh.15337
|View full text |Cite
|
Sign up to set email alerts
|

Is an 8‐week regimen of glecaprevir/pibrentasvir sufficient for all hepatitis C virus infected patients in the real‐world experience?

Abstract: Background and Aims:The revolution of the antiviral treatment of hepatitis C virus (HCV) infection resulting in higher effectiveness came with the introduction of direct-acting antivirals with pangenotypic regimens as a final touch. Among them, the combination of glecaprevir (GLE) and pibrentasvir (PIB) provides the opportunity for shortening therapy to 8 weeks in the majority of patients. Because of still insufficient evaluation of this regimen in the real-world experience, our study aimed to assess the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…Our findings on the very high effectiveness of GLE/PIB regardless of the history of previous therapies and liver fibrosis status supported the results of numerous clinical trials [33][34][35][36]. The excellent efficacy of 99-100% in GT1b patients, both noncirrhotic and cirrhotic, as well as treatmentnaïve and experienced, was also documented in published RWE studies [37][38][39][40][41]. Importantly, this option can be administered in renally impaired patients; two patients with kidney failure stage 4 and 5 treated within the current study responded to the therapy, which is consistent with published data [42].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings on the very high effectiveness of GLE/PIB regardless of the history of previous therapies and liver fibrosis status supported the results of numerous clinical trials [33][34][35][36]. The excellent efficacy of 99-100% in GT1b patients, both noncirrhotic and cirrhotic, as well as treatmentnaïve and experienced, was also documented in published RWE studies [37][38][39][40][41]. Importantly, this option can be administered in renally impaired patients; two patients with kidney failure stage 4 and 5 treated within the current study responded to the therapy, which is consistent with published data [42].…”
Section: Discussionsupporting
confidence: 83%
“…Rates of SVR12 were similar in the PP analysis of GT3‐ vs non‐GT3‐infected patients (97.9% vs 98.8%, respectively); GT3 patients had lower SVR12 in the ITT analysis (82.1% vs 88.8%) with equal patients LTFU. Another real‐world study evaluating 8‐week G/P therapy showed similar results in GT3 cirrhotics with 71.5% of F4 patients achieving SVR12% vs 98.5% of non‐GT3 infected patients; in F0‐F3 patients, 96.3% of GT3‐infected patients achieved SVR12% vs 98.6% of non‐GT3‐infected patients 11 . However, only seven GT3‐infected, F4 patients were included in the modified intention‐to‐treat (mITT) analysis vs 65 non‐GT3 patients.…”
Section: Discussionmentioning
confidence: 75%
“…The same effectiveness was documented by Lampertico et al following the 8-week GLE/PIB treatment duration in 19 cirrhotic patients with GT3 infection from seven small RWE studies included in the summary analysis [ 34 , 35 ]. A much lower SVR of 72% in PP analysis was demonstrated in nine GT3 infected cirrhotics in our previous study from the EpiTer-2 database, but it was due to a small subset of patients [ 36 ]. In the current study, 16 patients treated for 8 weeks achieved SVR, which gives an unsatisfactory rate of 84% in PP analysis, lower than demonstrated for a 12-week regimen with statistical significance for ITT analysis (80% vs. 95.4%, p = 0.05), however, it should be noted that a number of patients on 8-week regimen was still low.…”
Section: Discussionmentioning
confidence: 98%